Differences in MRI features between two different osteoarthritis subpopulations: data from the Osteoarthritis Initiative. Issue 5 (May 2016) - Roze, R.H.; Bierma-Zeinstra, S.M.A.; Agricola, R.; Oei, E.H.G.; Waarsing, J.H.
Summary: Objective: To investigate differences in MRI features between two etiologically distinct subtypes of knee osteoarthritis (OA): one group with metabolic syndrome and one lean group with frequent physical activity. Methods: We included two groups of 50 subjects of the Osteoarthritis Initiative (OAI) incidence subcohort, with KL ≥ 2 in at least one knee at 48 months follow-up. Inclusion criteria for the metabolic syndrome group were a body mass index (BMI) ≥ 30 kg/m 2 and two out of three of the following criteria: hypertension (RR > 130/85 mm Hg or hypertension medication), insulin resistance (high blood sugar or diabetic medication) or dyslipidemia (lipid lowering medication). Inclusion criteria for the active lean group were a BMI < 25 kg/m 2 and a Physical Activity Scale for the Elderly (PASE) score ≥ 2. MRI scans were scored using MR Imaging Osteoarthritis Knee Score (MOAKS). Differences in MOAKS items between groups were tested using generalized linear models adjusted for sex and age. Results: Scores for cartilage damage were significantly higher in the patella, trochlea and lateral femur in the metabolic syndrome group. Osteophyte scores were higher for all compartments in the metabolic syndrome group, though only significant for the patella, trochlea and medial tibia. Hoffa synovitis was significantly more prevalent in the active lean group while prepatellar bursa signal was more prevalent in the metabolic syndrome group. Conclusion: Metabolic OA and OA related to physical activity showed differences in MRI features, depending on knee compartment. These results show that different etiological processes in knee OA can lead to differences in structural degradation.